2019
DOI: 10.1051/e3sconf/20199706040
|View full text |Cite
|
Sign up to set email alerts
|

Development of construction waste management

Abstract: Improvement of building materials, optimization and development of technological processes of construction production require the development of promising areas of research to improve the efficiency of management of construction waste, which will provide economic and environmental benefits. The article provides statistical data on the volumes of formation and processing of construction and demolition waste, confirming the relevance and need for attention to the area of construction waste disposal. To improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Government has a key role to play in this regard. According to Aleksanin (2019), attention of government authorities should be focused toward appointing separate bodies to coordinate material and information flows across all RLSC actors. The negative impact of not having such bodies is evident in countries, such as Vietnam and China, where the lack of collection of C&DW information at a centralized level has resulted in poor waste recovery efforts (Kim et al, 2020;Wu et al, 2016).…”
Section: Inhibitors Of External Integration Across Dw Rlscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Government has a key role to play in this regard. According to Aleksanin (2019), attention of government authorities should be focused toward appointing separate bodies to coordinate material and information flows across all RLSC actors. The negative impact of not having such bodies is evident in countries, such as Vietnam and China, where the lack of collection of C&DW information at a centralized level has resulted in poor waste recovery efforts (Kim et al, 2020;Wu et al, 2016).…”
Section: Inhibitors Of External Integration Across Dw Rlscsmentioning
confidence: 99%
“…It is also the responsibility of the government to ensure enforcement of regulations by establishing systems of supervision to oversee all operations of the RLSC, clarify responsibilities of individual actors, and avoid conflicts (Liu et al, 2020b). Separate bodies can be appointed by the government to oversee the DW management process (Aleksanin, 2019). According to the author, these specialized bodies should be tasked with coordinating material and information resources by integrating the functions of all RLSC actors in terms of quantity, location, and timing.…”
Section: Measures For Improving External Integration In Dwrlscsmentioning
confidence: 99%
“…These activities generate massive amounts of CDW, causing environmental degradation, resource depletion and land deterioration (Islam et al , 2019). Therefore, there is a pressing need to implement an efficient and effective CDW management strategy that will lead to economic gains and protect the environment (Aleksanin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, Adewuyi, et al [9] revealed that the levels of material wastes generated on-site are in excess of estimator's allowance for some materials studied. Therefore, this study surveyed the factors influencing waste generation in building projects across southwestern states of Nigeria [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%